Acidulated phosphate fluoride sebagai bahan pencegahan Karies gigi anak : a scoping review (Laporan Penelitian) - Wafa Toriq Hayaza; Jeddy; Sri Ratna Laksmiastuti (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Caries occur in the hard tissues of the teeth due to bacterial activity in plaque. Untreated dental caries can result in pain, therefore early and if caries is left over time it will cause pain so that early caries prevention is necessary. Caries prevention can be done using Acidulated Phosphate Fluoride as an effective option in preventing the process of caries development in children. Aim: To know the effectiveness of APF gel 1,23% in preventing caries in children. Method: Scoping Review with inclusion criteria using a Randomized Controlled Trial (RCT) study design was conducted according to Preferres Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and two databases (PubMed and Google Scholar). Result: The results showed that the initial search yielded 985 documents. After eliminating duplicate studies and screening full-text articles for eligibility (n = 21), the authors identified 3 studies that met the criteria for inclusion. Conclusion: APF gel 1.23% has the effectiveness and preventing dental caries in children due to its better ability to bind calcium enamel,also does not irritate the gingiva..